Factors Influencing Civil Servants' Interest in Whistleblowing Intentions: A Study at the Bureau of Government, Regional Autonomy, and Regional Secretariat Cooperation, Central Java Province - Hardanti, Okta Karina; Januarti, Indira (GoAcademica Research & Publishing, 2025)
This study is to examine and present empirical data on individual elements, including attitudes, subjective norms, perceived behavioral control, moral intensity, and professional dedication, that influence employee intent to whistleblowing. This research has a quantitative nature which was carried out using the help of the IBM SPSS program. The sample in this study was 60 workers of the Biro Pemerintahan, Otonomi Daerah dan Kerjasama Sekretariat Daerah Provinsi Jawa Tengah as a whole. These findings showed a significant relationship between attitudes, subjective norms, moral intensity, professional commitment and whistleblowing intention whereas perceptions of behavioral control were not significant to whistleblowing intention. Therefore, the phenomenon of whistleblowing intentions in the Biro Pemerintahan, Otonomi Daerah dan Kerjasama Sekretariat Daerah Provinsi Jawa Tengah can be explained by the theory of planned behavior.